Single dose testosterone increases total cholesterol levels and induces the expression of HMG CoA Reductase - Gårevik Nina; Skogastierna Cristine; Rane Anders; Ekström Lena (BMC, 2012)
Abstract Background Cholesterol is mainly synthesised in liver and the rate-limiting step is the reduction of 3-hydroxy-3methylglutaryl coenzyme A (HMG-CoA) to mevalonate, a reaction catalysed by HMG-CoA reductase (HMGCR). There is a comprehensive body of evidence documenting that anabolic-androgenic steroids are associated with deleterious alterations of lipid profile. In this study we investigated whether a single dose of testosterone enanthate affects the cholesterol biosynthesis and the expression of HMGCR. Methods 39 healthy male volunteers were given 500 mg testosterone enanthate as single intramuscular dose of Testoviron®--Depot. The total cholesterol levels prior to and two days after testosterone administration were analysed. Protein expression of HMGCR in whole blood was investigated by Western blotting. In order to study whether testosterone regulates the mRNA expression of HMGCR, in vitro studies were performed in a human liver cell-line (HepG2). Results The total cholesterol level was significantly increased 15% two days after the testosterone injection (p = 0.007). This is the first time a perturbation in the lipoprotein profile is observed after only a single dose of testosterone. Moreover, the HMGCR mRNA and protein expression was induced by testosterone in vitro and in vivo, respectively. Conclusion Here we provide a molecular explanation how anabolic androgenic steroids may impact on the cholesterol homeostasis, i.e. via an increase of the HMGCR expression. Increasing knowledge and understanding of AAS induced side-effects is important in order to find measures for treatment and care of these abusers.